Gender equality in local authorities of Zimbabwe: the case of Gweru municipality from 2008 to 2015 - Zimbudzana, Caroline Ngaatendwe (Midlands State University, 2017)
Equality as a concert of sexes is a relatively current observable fact. From the late nineteenth century to date many conventions, policies and institutions have arisen in a bid to promote the equality of man and women. This research was undertaken in an effort to analyse the level at which Local Authorities in Zimbabwe with specific reference to Gweru Municipality, have managed to uphold and achieve 50% equality between men and women in council elections. The research was a significant endeavor in encouraging responsible actors and policy makers to go an extra mile in promoting and archiving gender equality. With the adequate use of qualitative and quantitative analysis, the researcher made use of random sampling, specific case study, questioners and interviews. The main center of concern was to acquire if the populace know the meaning of gender equality, if relevant actors and institutions are playing their part and what the situation has been of late and currently. Unfortunately gender equality from the study can be concluded to be lying at 20% women against 80% men. However important statistical records were also missing from responsible offices for instance ZEC. The research prompts the rethinking and structuring of certain domestic policies as well as the efficiency of institutions which uphold gender equality.